Coaching communication issues with elite female athletes: Two Norwegian case studies - Kristiansen, E.; Tomten, S. E.; Hanstad, D. V.; Roberts, G. C. (Scandinavian Journal of Medicine & Science in Sports, 2012)
The aim of this study was to examine the careers of two successful female elite athletes who later stagnated, and to identify possible factors that might have led to their demotivation. Individual interviews and a focus group interview were conducted. Using a multidisciplinary approach, the stories of April and Hazel raised several issues related to coaching, coach education, and the development of female athletes. Their individual profiles revealed that their perception of the lack of long-term development was caused by coach miscommunication, having to cope with sudden fame, and injuries provoked by overtraining. The coach-athlete relationship was discussed with a focus on the inexperience of some coaches, the number of coaches the athletes had to deal with, sociolinguistic issues, and the differing criteria of success communicated. Finally, the importance of their national governing bodies to focus on knowledge transfer, the supervision of coaches, and the infrastructure to monitor athletes were discussed.